2015
DOI: 10.1128/jb.00529-15
|View full text |Cite
|
Sign up to set email alerts
|

Aconitase Functions as a Pleiotropic Posttranscriptional Regulator in Helicobacter pylori

Abstract: Posttranscriptional regulation in bacteria has increasingly become recognized as playing a major role in response to environmental stimuli. Aconitase is a bifunctional protein that not only acts enzymatically but also can be a posttranscriptional regulator. To investigate protein expression regulated by Helicobacter pylori AcnB in response to oxidative stress, a global proteomics study was conducted wherein the ⌬acnB strain was compared to the parent strain when both strains were O 2 stressed. Many proteins, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…In particular, the abundance of AhpC was significantly lower in the acnB strain compared to the wild-type (Austin, Wang and Maier 2015). The acnB mutant also displayed decreased survival during exposure to atmospheric O 2 as well as hypersensitivity towards cumene hydroperoxide (Austin, Wang and Maier 2015).…”
Section: Aconitasementioning
confidence: 94%
See 1 more Smart Citation
“…In particular, the abundance of AhpC was significantly lower in the acnB strain compared to the wild-type (Austin, Wang and Maier 2015). The acnB mutant also displayed decreased survival during exposure to atmospheric O 2 as well as hypersensitivity towards cumene hydroperoxide (Austin, Wang and Maier 2015).…”
Section: Aconitasementioning
confidence: 94%
“…The acnB mutant also displayed decreased survival during exposure to atmospheric O 2 as well as hypersensitivity towards cumene hydroperoxide (Austin, Wang and Maier 2015). Binding of apo-AcnB to the 3 UTR of the ahpC transcript was confirmed by electrophoretic mobility shift assay (EMSA) (Austin, Wang and Maier 2015).…”
Section: Aconitasementioning
confidence: 95%
“…In H. pylori, some of those are connected to sensing performed by TlpD (Behrens et al, 2016). The authors identified several novel intracellular protein interaction partners of TlpD by mass spectrometry, including the iron-sulfur cluster-containing enzyme aconitase (AcnB) (Austin et al, 2015;Behrens et al, 2016). Besides the metabolic enzyme AcnB and the chemotaxis histidine kinase CheAY2, catalase KatA was detected as direct physical interactor of TlpD.…”
Section: Modulation Of Motility and Taxis By Co-regulatory Protein-prmentioning
confidence: 99%
“…Conversely, TlpD had an effect on transcriptional regulation, impacting the expression of numerous genes involved in redox homeostasis and metabolism (Behrens et al, 2016). Therefore, it has been hypothesized that TlpD could serve as a linker between the taxis response and metabolic regulatory responses, possibly via the bifunctional regulatory protein AcnB (Austin et al, 2015;Behrens et al, 2016) (see next chapter for AcnB regulatory function). This direct link might be required to cope with energy limitation conditions, thus providing an immediate mechanism to improve the intracellular state of the cell.…”
Section: Modulation Of Motility and Taxis By Co-regulatory Protein-prmentioning
confidence: 99%
See 1 more Smart Citation